Internal fixation of fracture of femur of dog using intramedullary pinning (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The study was conducted at S A Quadery Teaching Veterinary Hospital (SAQTVH) in Chittagong Veterinary and Animal Sciences University (CVASU), Bangladesh from January, 2014 to June 2014 to conduct about the surgical management of internal fixation of fracture of femur of local dog using intramedullary pinning. A total number of 10 dogs of different ages were used for surgical management based on history and presenting clinical sings. Fractures of femur commonly occur in dogs following different kind of trauma, road accident and jumping from top place. In the small animal internal fracture fixation, many improvements have been developed, including improved fixation techniques and a more diverse selection of implants. To treat this fractures intramedullary pin are used for internal surgical fixation with clinical and radiological procedure established. After successful surgical repair bone healing was occurred without any complications and the dog discharged one month after surgery bearing weight on the limb.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 243-246